2006
DOI: 10.1016/s0022-5347(05)00700-7
|View full text |Cite
|
Sign up to set email alerts
|

Healthy, Middle-Aged, History-Free, Continent Women—Do They Strain to Void?

Abstract: These healthy middle-aged women without a history of pelvic surgery, or symptoms or signs of urological, anorectal or gynecological problems, voided with a mean Pdetmax of 25 cm H(2)O, mean Qmax of 29 ml per second, and the majority without residual. Many of them strained during detrusor contraction and this had not led to the development of signs or symptoms. The way straining is done may make the difference in that during reflex bladder contraction and urethral relaxation, additional straining may have littl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(39 citation statements)
references
References 15 publications
1
38
0
Order By: Relevance
“…All 12 patients with bilateral dilating reflux had this activity, but only 5 of 10 patients with non-dilatating bi or unilateral reflux had it (P ¼ 0.005). As Pauwels et al, 22 did not find any increase in surface EMG recordings during pQ study even when straining in healthy middle-aged women, our findings are probably caused by true dysfunction of the sphincter. Also a marginally significant difference (P ¼ 0.074) was detected in cystometric large residuals when comparing patients with earlier bilateral dilating reflux (residual over 100 ml in six patients) to those with earlier non-dilating bi or unilateral reflux (residual over 100 ml in one patient).…”
Section: Discussionsupporting
confidence: 65%
“…All 12 patients with bilateral dilating reflux had this activity, but only 5 of 10 patients with non-dilatating bi or unilateral reflux had it (P ¼ 0.005). As Pauwels et al, 22 did not find any increase in surface EMG recordings during pQ study even when straining in healthy middle-aged women, our findings are probably caused by true dysfunction of the sphincter. Also a marginally significant difference (P ¼ 0.074) was detected in cystometric large residuals when comparing patients with earlier bilateral dilating reflux (residual over 100 ml in six patients) to those with earlier non-dilating bi or unilateral reflux (residual over 100 ml in one patient).…”
Section: Discussionsupporting
confidence: 65%
“…Abdominal straining to void is considered unhealthy by researchers because of its association with poor outcomes, such as fecal and/or urinary incontinence [34], dysfunctional voiding [13], and prolonged postoperative catheterization [35]. Pauwels et al indicated that if straining was used to begin voiding before the initiation of the micturition reflex and as the only way to empty bladder, voiding problems and incontinence are more likely to occur [11]. …”
Section: Discussionmentioning
confidence: 99%
“…Straining to empty the bladder, which involves an abdominal muscle contraction, could increase the peak flow and mean flow rates, as well as decrease the total voiding time [10]. Individuals who use straining to start voiding before the initiation of the micturition reflex may be more likely to develop incontinence and voiding dysfunction [11]. Toileting behavior is a comprehensive concept that includes voiding place, time, position, and style [12]; however, most recent studies on toileting behavior and overactive bladder focused only on one or some aspects of toileting behavior [13, 14].…”
Section: Introductionmentioning
confidence: 99%
“…A study by Pauwels et al [17] found that 41 % of middle-aged women without urinary symptoms used abdominal pressure to urinate. Some authors do not consider this type of urination as pathological.…”
Section: Discussionmentioning
confidence: 99%